Aortic valve disease. Issue 10 (4th June 2014) - Rayner, J.; Coffey, S.; Newton, J.; Prendergast, B. D.
Summary Aortic valve disease is common and has significant impact on prognosis and quality of life. In this educational review, we cover the pathophysiology, presentation and assessment of aortic stenosis (AS) and aortic regurgitation (AR), including the role of imaging modalities beyond echocardiography. We review current treatment strategies and emphasise the use and indications for transcatheter aortic valve implantation (TAVI) in view of recent data highlighting its emergence as a novel treatment option for patients with AS, who are unsuitable for conventional aortic valve replacement (AVR). We also describe novel surgical approaches for AR and potential future strategies for percutaneous intervention.